(untitled) (The Research of Medical Science Review, 2024)
FND is caused by specific neurological signs and symptoms, however a definitive underlying pathology is not apparent, Despite the high frequency, FND has been neglected and often dismissed in the medical realm. This study aims to look into doctors’ perceptions of FND with the goal of improving patient experience and treatment. A total of 152 doctors from different specialties participated in the research, which employed a cross-sectional survey. The survey included multiple-choice questions about the diagnosis and management of FND in addition to the doctors’ opinion on firsthand experience. Electronic forms were used for data collection and the analysis consisted of descriptive and thematic space types. Thoughts about FND were polar among the participants. Some were dismissive and labelled the doctors participating, whilst neurology and psychiatry professionals have had a more rounded comprehension of the disorder. It is known that an increasing number of medical doctors regularly come across FND patients, making its thorough understanding rather relevant. However, certain problems with classification, evaluation methods and even the interrelation were obvious. Different methods of treatment insight the need to tailor treatment approach to individual needs of the patients. In this survey, the difference in opinions on management of FND between the doctors has been presented. Persistent misinterpretation and communication barriers still exist, even with greater focus. These findings underscore the value of continuing medical education, anti-stigma efforts and collaboration.